2017
DOI: 10.1038/tp.2017.132
|View full text |Cite|
|
Sign up to set email alerts
|

Disrupted hippocampal neuregulin-1/ErbB3 signaling and dentate gyrus granule cell alterations in suicide

Abstract: Neuregulin-1 (NRG1) and ErbB receptors have been associated with psychopathology, and NRG1-ErbB3 signaling has been shown to increase hippocampal neurogenesis and induce antidepressant-like effects. In this study, we aimed to determine whether deficits in NRG1 or ErbBs might be present in the hippocampus of suicide completers. In well-characterized postmortem hippocampal samples from suicides and matched sudden-death controls, we assessed gene expression and methylation using qRT-PCR and EpiTYPER, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…Altered production and survival of developmentally‐born DG neurons is also relevant for a number of disorders that are associated with large‐scale structural changes in the hippocampus, and sometimes the DG in particular, such as autism (Saitoh, Karns, & Courchesne, ; Schumann et al, ), schizophrenia (Lodge & Grace, ; Tamminga, Stan, & Wagner, ) and depression (McKinnon, Yucel, Nazarov, & MacQueen, ). For example, recent reports indicate that depressed patients have fewer total DG neurons in the anterior hippocampus, which can be restored by SSRI antidepressants (Boldrini et al, ; Mahar et al, ). While antidepressant treatments are often cited for their proneurogenic properties, our findings indicate that changes in the developmentally‐born cell population could also contribute to changes in total granule cell number.…”
Section: Discussionmentioning
confidence: 99%
“…Altered production and survival of developmentally‐born DG neurons is also relevant for a number of disorders that are associated with large‐scale structural changes in the hippocampus, and sometimes the DG in particular, such as autism (Saitoh, Karns, & Courchesne, ; Schumann et al, ), schizophrenia (Lodge & Grace, ; Tamminga, Stan, & Wagner, ) and depression (McKinnon, Yucel, Nazarov, & MacQueen, ). For example, recent reports indicate that depressed patients have fewer total DG neurons in the anterior hippocampus, which can be restored by SSRI antidepressants (Boldrini et al, ; Mahar et al, ). While antidepressant treatments are often cited for their proneurogenic properties, our findings indicate that changes in the developmentally‐born cell population could also contribute to changes in total granule cell number.…”
Section: Discussionmentioning
confidence: 99%
“…Although, herein, the description of NRGs/ErbB-dependent roles in the modulation of synaptic plasticity has been focused on the hippocampus and midbrain DA nuclei, it should be considered that emerging evidence also documented NRGs-induced regulation of synaptic plasticity in other brain areas, and several reports mainly obtained in transgenic mice with altered NRGs/ErbB signaling support that the proper NRGs/ErbB tone (neither too much nor too little) is essential for various cognitive functions and behaviors. Since dysfunctions in NRGs/ErbB signaling have been linked to different neurological and psychiatric disorders, including schizophrenia, bipolar disorder, autism spectrum disorders, genetic intellectual disabilities, AD, major depressive disorder, PD, and addiction [23,46,[136][137][138][139][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159], intense research efforts should be aimed at deciphering NRGs-dependent mechanisms causing pathological defects, as this might have noticeable implications on the understanding and treatment of different serious brain diseases.…”
Section: Conclusion and Outstanding Issuesmentioning
confidence: 99%
“…The functional relevance of this delayed cell death is unknown, but it could contribute to forgetting and hippocampal/DG atrophy in disorders such as depression (Boldrini et al, 2013;Mahar et al, 2017;McKinnon, Yucel, Nazarov, & MacQueen, 2009). Also, while adult-born neurons are stable after reaching 4 weeks of age, we found that 17% of P6-born neurons died between 2 and 6 months of age.…”
mentioning
confidence: 99%
“…Also, while adult-born neurons are stable after reaching 4 weeks of age, we found that 17% of P6-born neurons died between 2 and 6 months of age. The functional relevance of this delayed cell death is unknown, but it could contribute to forgetting and hippocampal/DG atrophy in disorders such as depression (Boldrini et al, 2013;Mahar et al, 2017;McKinnon, Yucel, Nazarov, & MacQueen, 2009). Whether delayed cell death is observed among cells born at ages other than P6 is unknown.…”
mentioning
confidence: 99%